Integrated of Gravity and Magnetic Data to Modeling Structure Subsurface In Bora Geothermal Field Central Sulawesi. (August 2019) - Efendi, Rustan; Abdullah,; Syamsuddin, Erfan; Rusydi, M.; Nirmayanti,; Sugianto, Asep; Joni, Wiwid
Abstract: This field research is located in a geothermal area expressed by the existence of hot springs. A complex geological structure has shown that the area was in the Palu-Koro fault. The purpose of the study is to achieve a model of subsurface of the area using data collected over gravity data and magnetic data. The two Data were compared in order to validate the models. Furthermore 2-dimensional modeling was performed using two gravity and magnetic lines by means of geo-sys software from Geosoft. The results of the models have a bit difference response by means of the existence of residual indicator that expected as a geothermal reservoir due to fault activity